Tidal stream resource assessment uncertainty due to flow asymmetry and turbine yaw misalignment. (December 2017) - Piano, M.; Neill, S.P.; Lewis, M.J.; Robins, P.E.; Hashemi, M.R.; Davies, A.G.; Ward, S.L.; Roberts, M.J.
Abstract: The majority of tidal energy convertors (TECs) currently under development are of a non-yawing horizontal axis design. However, most energetic regions that have been identified as candidate sites for installation of TEC arrays exhibit some degree of directional and magnitude asymmetry between incident flood and ebb flow angles and velocities, particularly in nearshore environments where topographic, bathymetric and seabed frictional effects and interactions are significant. Understanding the contribution of directional and magnitude asymmetry to resource power density along with off axis rotor alignment to flow could influence site selection and help elucidate optimal turbine orientation. Here, 2D oceanographic model simulations and field data were analysed to investigate these effects at potential deployment locations in the Irish Sea; an energetic semi-enclosed shelf sea region. We find that observed sites exhibiting a high degree of asymmetry may be associated with a reduction of over 2% in annual energy yield when deployment design optimisation is ignored. However, at the majority of sites, even in the presence of significant asymmetry, the difference is <0.3%. Although the effects are shown to have less significance than other uncertainties in resource assessment, these impacts could be further investigated and quantified using CFD and 3D modelling. Highlights: Flow direction and magnitude asymmetry on tidal stream resource is quantified. Turbine yaw misalignment combined with tidal asymmetry is further assessed. 2D oceanographic models and field data are used to investigate these effects. Formulation of a simple spatial assessment methodology is presented. Reduction of over 2% in turbine annual energy yield when optimisation ignored.